Acrylate modified polyurethane hot melt adhesive as well as preparation method and application thereof
Polyurethane prefabricated polyurethane prefabricated polyurethane prefabricated polyurethane compounds and isocyanate compounds are used in polyurethane thermal melting glue, and acrylic compounds and ionic liquids are introduced to solve the difficulty of applying glue and adhesion intensity at room temperature at room temperature at room temperature. Low problems, polyurethane modified thermal melting glue with room temperature point glue, high adhesion intensity, and electrical disassembly function.
Patent Information
- Application Number
- CN202411460621.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-18
AI Technical Summary
Existing polyurethane hot melt adhesives are difficult to apply at room temperature, with high melt viscosity, low bonding strength, and difficult to achieve easy disassembly function.
By using a low viscosity polymiocyte compound and isocyanate -type compound reaction to prepare a polyurethane pre -polymer mixture at the biopygalized end of the galcus, and introduce acrylic compounds and ionic liquids in this mixture, control the prefabricated polyurethane prefabricated and acrylic compounds Compared to reducing the viscosity of the system, increasing adhesion intensity, and giving electrical disassembly function.
It realizes low-viscosity dispensing of polyurethane hot-melt adhesive at room temperature, with high initial and final bonding strength, fast curing speed, and detachable function when powered on, which reduces the glue threshold and equipment costs, and improves safety.
Smart Images

Figure BDA0005091765290000191
Abstract
Description
Technical Field
[0001] The invention belongs to the field of adhesives, and in particular relates to an acrylate-modified polyurethane hot-melt adhesive and a preparation method and application thereof. Background Art
[0002] Reactive polyurethane hot melt adhesive is often used to bond and fix electronic product components in electronic products such as smartphones, tablets, smart watches, and TWS headsets. Electronic product components bonded with reactive polyurethane hot melt adhesives are often of high value. When poor assembly, after-sales product repairs, or recycling of valuable electronic product components occur, it is usually necessary to disassemble some of the bonded components. Therefore, the adhesive is usually required to have excellent bonding reliability while being easy to disassemble under certain conditions.
[0003] Reactive polyurethane hot melt adhesive is mainly composed of isocyanate-terminated oligomers. The isocyanate groups in the isocyanate-terminated oligomers can react with moisture in the air and form a cross-linked chemical structure after complete curing, thereby achieving high bonding strength. However, the covalent bonds obtained by the reaction of isocyanate groups with moisture are irreversible, and the cross-linked structure is difficult to destroy. It is usually difficult to disassemble the adhesive after complete curing. If the bonded materials need to be separated, it is often necessary to use large external forces, high temperatures, chemical reagents and other conditions, and the bonded materials may be damaged during the disassembly of the adhesive, resulting in large economic losses.
[0004] In recent years, there are also technologies that add ionic liquids or alkali metal salts and solvated matrices to polyurethane hot melt adhesives to give polyurethane hot melt adhesives the function of being disassembled under power-on conditions. However, although the existing electrically disassembled polyurethane hot melt adhesives have the function of being disassembled under power-on conditions, due to the high melt viscosity of such polyurethane hot melt adhesives, they are a solid substance at room temperature and usually need to be heated to a melting temperature (usually 90°C to 160°C) or above before they can be extruded and glued. At this time, it is generally necessary to equip and use professional heating glue-applying equipment, but this will greatly limit the application scenarios of such polyurethane hot melt adhesives while increasing the cost of glue. For example, it is inconvenient to use such polyurethane hot melt adhesives in places such as homes and repair markets where it is inconvenient to equip heating equipment, thereby greatly limiting the wide application and promotion of such polyurethane hot melt adhesives. Furthermore, although the existing electrically disassembled polyurethane hot melt adhesives have certain electrically disassembled functions, the final bonding strength is low, the reliability is poor, and the curing speed is slow. There is a large performance gap with the traditional reactive polyurethane hot melt adhesive, and it is difficult to meet the performance requirements of actual application scenarios.
[0005] The existing acrylate-modified polyurethane hot melt adhesive is a polyurethane hot melt adhesive that can be UV-humidity dual-cured and prepared by modifying the polyurethane hot melt adhesive by physical blending or chemical modification of acrylate compounds. The UV curing speed is fast. After UV light exposure, the acrylate components in the acrylate-modified polyurethane hot melt adhesive can be quickly photocured, effectively improving the defect of the polyurethane hot melt adhesive that relies on moisture to cure slowly. However, the acrylate-modified polyurethane hot melt adhesive still has many problems such as being difficult to disassemble after curing and difficult to apply glue at room temperature.
[0006] In summary, there is an urgent need to develop an adhesive with low melt viscosity, which can be dispensed at room temperature, has high initial and final bonding strengths, fast curing speed and electrical disassembly function to meet the application needs of the market. Summary of the invention
[0007] The first object of the present invention is to provide an acrylate modified polyurethane hot melt adhesive which has low melt viscosity, can be dispensed at room temperature, has high initial bonding strength and final bonding strength, has a fast curing speed and can be electrically disassembled.
[0008] The second object of the present invention is to provide a method for preparing the above-mentioned acrylate-modified polyurethane hot melt adhesive.
[0009] The third object of the present invention is to provide the application of the above-mentioned acrylate modified polyurethane hot melt adhesive in the bonding of electronic products.
[0010] Specifically, the acrylate-modified polyurethane hot melt adhesive provided by the present invention has a viscosity range of 1000 to 150000 cps at 25°C and a bonding strength attenuation rate of more than 80% after a voltage of 1 to 100 V is applied. The acrylate-modified polyurethane hot melt adhesive contains a polyurethane prepolymer mixture, an acrylate compound, an ionic liquid and a photoinitiator. Both ends of the prepolymer contained in the polyurethane prepolymer mixture are capped with isocyanate. The polyol structural unit contained in the polyurethane prepolymer mixture is derived from a low-viscosity polyol compound having a glass transition temperature of less than 0°C and a melting point of less than 40°C. The mass ratio of the polyurethane prepolymer mixture to the acrylate compound is (1.5 to 9):1.
[0011] The preparation method of the acrylate modified polyurethane hot melt adhesive provided by the present invention comprises:
[0012] S1, dehydrating the low-viscosity polyol compound and the ionic liquid and the optional rheology modifier, silane coupling agent and water absorbent to obtain a pretreated product;
[0013] S2, stirring the pretreated product, the polyisocyanate compound and the optional catalyst at 70-90° C. for 1-5 hours to obtain a prepolymer containing a polyurethane prepolymer mixture;
[0014] S3. Evenly mix the prepolymer, the acrylate compound and the photoinitiator to obtain the acrylate-modified polyurethane hot melt adhesive.
[0015] After in-depth and extensive research, the inventors of the present invention have found that the polyurethane polymer with isocyanate functional groups used in the existing electrically disassembled polyurethane hot melt adhesive is a polyurethane prepolymer obtained by reacting a polyol compound with an excess of polyisocyanate compounds. The molar equivalent ratio of isocyanate groups in such polyisocyanate compounds to hydroxyl groups in polyol compounds is usually set at (1.5-2.5):1 (i.e., the molar ratio of NCO / OH is (1.5-2.5):1). The polyurethane prepolymer prepared according to this stoichiometric relationship has a low isocyanate content, a large molecular weight, and a large interaction force between molecular chains, resulting in the final polyurethane prepolymer having a high melt viscosity and being difficult to dispense at room temperature. In addition, some polyol compounds used in such polyurethane prepolymers with isocyanate functional groups have strong crystallinity or a high glass transition temperature (Tg) at room temperature, and the polyurethane prepolymer prepared by reacting room temperature crystalline polyols or high Tg polyols with isocyanate compounds is usually a solid substance at room temperature. Therefore, the electrically degradable polyurethane hot melt adhesive currently prepared by traditional methods is usually a solid substance at room temperature and needs to be heated to above the melting point (90°C to 160°C) before it can be melted and applied. This greatly increases the threshold for using such polyurethane hot melt adhesives, increases the cost of adhesive equipment, and also increases the risk of operators being burned during the adhesive application process.
[0016] The existing electrically disassembled polyurethane hot melt adhesive is to add ionic liquid or alkali metal salt and solvated matrix to the polyurethane hot melt adhesive, and utilize the Faraday reaction of anions and cations in the ionic liquid or alkali metal salt under the condition of power on, so as to give the polyurethane hot melt adhesive the function of disassembly under the condition of power on. Among them, although the liquid substances such as ionic liquid and solvated matrix introduced into the polyurethane hot melt adhesive are conducive to realizing the function of electrical disassembly, such liquid substances cannot participate in the curing of the polyurethane hot melt adhesive, and still exist in the state of initial low viscosity after the polyurethane hot melt adhesive is cured, so it has a certain negative effect on the final bonding strength of the adhesive. In addition, since the equivalent ratio of isocyanate to hydroxyl in the current isocyanate-terminated polyurethane prepolymer is relatively low (the equivalent ratio of NCO / OH is between 1.5 and 2.5), the isocyanate content of the polyurethane prepolymer finally obtained is low, so the crosslinking density of such polyurethane prepolymer after the final wet curing is low, so that the adhesive itself has a low bonding strength after curing, and the bonding strength will be further reduced after being negatively affected by the liquid components such as ionic liquid and solvated matrix. Therefore, although the electrically disassembled polyurethane hot melt adhesive can be prepared by adding ionic liquid or alkali metal salt in combination with a solvating matrix to the polyurethane hot melt adhesive, its final adhesion still has great deficiencies, which is not conducive to the application and promotion of such products.
[0017] Although the existing acrylate-modified polyurethane hot melt adhesive can increase the curing speed and effectively improve the defect of the slow curing speed of the polyurethane hot melt adhesive relying on moisture, the bonding force formed after curing is relatively strong, and it is difficult to achieve the function of easy disassembly. In addition, the adhesives that can achieve electrical disassembly generally require that the bonding substrate needs to be conductive. Usually, such conductive substrates are all opaque substrates such as stainless steel, aluminum, copper and other metals. For the bonding of opaque substrates, it is difficult to use UV light-curing adhesives and UV moisture-curing adhesives with UV light-curing components such as acrylate compounds as the main body in the usual sense. This is because after UV light, the adhesive composition with light-curing components as the main body will instantly cure after UV light, and quickly lose re-adhesion after UV light. Therefore, most UV light-curing adhesives or UV moisture-curing adhesives can only be used for bonding substrates with at least one side transparent. Therefore, even if the known electrical disassembly composition that can provide electrical disassembly function is directly added to the existing UV acrylate adhesive or UV moisture-curing adhesive with UV acrylate compounds as the main body, it is difficult to directly apply it to the bonding of opaque metal substrates. In addition, some existing acrylate-modified polyurethane hot melt adhesives that can be used for bonding opaque substrates are mainly composed of polyurethane prepolymers as the main component, with a small amount of acrylate compounds for modification. Although such acrylate-modified polyurethane hot melt adhesives can be used for bonding opaque substrates, the melt viscosity of such acrylate-modified polyurethane hot melt adhesives is relatively high, and usually heating equipment is still required for dispensing. The reason why such acrylate-modified polyurethane hot melt adhesives are difficult to apply at room temperature is mainly that on the one hand, the proportion of low-viscosity acrylate compounds is small, and the dilution ability of the polyurethane prepolymer body is weak. On the other hand, the preparation process of the polyurethane prepolymer itself still uses some polyol compounds with relatively high glass transition temperatures and / or relatively strong crystallinity at room temperature, and the melt viscosity of such polyurethane prepolymer body itself is relatively high. Therefore, the acrylate-modified polyurethane hot melt adhesive finally prepared is difficult to melt and dispense at room temperature, and heating equipment is required for dispensing.
[0018] The key to the present invention is to prepare an isocyanate-dicapped polyurethane prepolymer mixture by reacting a polyol compound with a low glass transition temperature and low crystallinity at room temperature with an excess of isocyanate compounds, and innovatively introduce acrylate compounds and ionic liquids into the polyurethane prepolymer mixture, while strictly controlling the ratio between the polyurethane prepolymer mixture and the acrylate compounds, thereby giving the final acrylate-modified polyurethane hot melt adhesive the advantages of low melt viscosity, dispensing at room temperature, high initial and final bonding strengths, fast curing speed, and electrical disassembly. It is speculated that the reason may be that: acrylate compounds and ionic liquids have good fluidity at room temperature and both have low viscosity. The simultaneous introduction of acrylate compounds and ionic liquids into the polyurethane hot melt adhesive can achieve the "initial" reduction in the viscosity of the system and improve the fluidity of the adhesive at room temperature. The selection of low-viscosity polyol compounds with a glass transition temperature below 0°C and a melting point below 40°C can fundamentally reduce the melt viscosity of the polyurethane prepolymer at room temperature and achieve a "secondary" reduction in the viscosity of the system. That is, the present invention reduces the viscosity of the system from two dimensions: the synergistic external viscosity reduction of acrylate compounds / ionic liquids and the internal viscosity reduction of the polyurethane prepolymer. This is conducive to the direct application of polyurethane hot melt adhesive at room temperature, greatly lowers the application threshold of polyurethane hot melt adhesive, reduces the equipment cost required for the application of polyurethane hot melt adhesive, and effectively avoids the risk of operators being scalded during the glue application process. Furthermore, the acrylate compound can rapidly undergo free radical polymerization after UV irradiation, quickly establish a high initial bonding strength, and then the polyurethane prepolymer further improves the system bonding strength through moisture curing reaction, and can form a polyurethane-polyacrylate interpenetrating network structure after curing, giving the polyurethane hot melt adhesive a higher final bonding strength. In addition, the Faraday reaction that can occur in the ionic liquid after power is turned on can give it an electrically disassembled property by introducing an ionic liquid into the acrylate-modified polyurethane hot melt adhesive. Furthermore, as described above, the polyurethane hot melt adhesive provided by the present invention relies on acrylate compounds to improve the initial bonding strength in the early stage, and relies on the polyurethane-polyacrylate interpenetrating network structure to improve the final bonding strength in the later stage. Even if it is affected by the uncured ionic liquid, it can still maintain a relatively high initial bonding strength and final bonding strength. DETAILED DESCRIPTION
[0019] The viscosity of the acrylate modified polyurethane hot melt adhesive provided by the present invention at 25° C. ranges from 1000 to 150000 cps, specifically 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, 30000, 50000, 70000, 90000, 110000, 130000, 150000 cps or any value therebetween.
[0020] The attenuation rate of the bonding strength of the acrylate modified polyurethane hot melt adhesive provided by the present invention after being energized at a voltage of 1 to 100 V is above 80%, and can specifically be 80%, 82%, 85%, 88%, 90%, 92%, 95%, 98%, 99%, 100% or any value therebetween. The voltage required for the electrical disassembly of the acrylate modified polyurethane hot melt adhesive is preferably 1-100V, specifically 1V, 3V, 5V, 7V, 9V, 10V, 20V, 30V, 40V, 50V, 60V, 70V, 80V, 90V, 100V or any value therebetween; the time required for electrical disassembly is preferably 1s-60min, such as 1s, 2s, 5s, 15s, 30s, 40s, 50s, 1min, 5min, 10min, 15min, 20min, 30min, 40min, 50min, 60min or any value therebetween.
[0021] In the present invention, the acrylate-modified polyurethane hot melt adhesive contains a polyurethane prepolymer mixture, an acrylate compound, an ionic liquid and a photoinitiator. The viscosity of the system is reduced by introducing a polyol structural unit with weaker crystallinity or lower glass transition temperature in the polyurethane prepolymer mixture and adding an acrylate compound and an ionic liquid, thereby giving it the performance of direct gluing at room temperature. Furthermore, the initial bonding strength and curing speed of the polyurethane hot melt adhesive are improved by introducing an acrylate compound, the final bonding strength is improved by controlling the mass ratio of the polyurethane prepolymer mixture to the acrylate compound, and the polyurethane hot melt adhesive is given the performance of electrical disassembly by introducing an ionic liquid. The polyol structural unit contained in the polyurethane prepolymer mixture is derived from a low-viscosity polyol compound. Among them, the glass transition temperature (Tg) of the low-viscosity polyol compound is below 0°C, specifically 0°C, -2°C, -4°C, -6°C, -8°C, -10°C, -12°C, -14°C, -16°C, -18°C, -20°C, -22°C, -24°C, -26°C, -28°C, -30°C, -32°C, -34°C, -36°C, -38°C, -40°C, etc. The melting point of the low-viscosity polyol compound is below 40°C, and can be 40°C, 38°C, 36°C, 34°C, 32°C, 30°C, 28°C, 26°C, 24°C, 22°C, 20°C, 18°C, 16°C, 14°C, 12°C, 10°C, 8°C, 6°C, 4°C, 2°C, 0°C, -5°C, -10°C, -15°C, -20°C, -30°C, etc. The mass ratio of the polyurethane prepolymer mixture to the acrylate compound is (1.5-9.0):1, and can be 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1 or any value therebetween. In the present invention, the term "polyurethane prepolymer mixture" refers to a prepolymer obtained by an addition reaction of a polyisocyanate compound and a low-viscosity polyol compound. Since the prepolymer contains polymers of different molecular weights and possible unreacted monomers, it is a mixture of multiple substances and is therefore called a "polyurethane prepolymer mixture."
[0022] The acrylate modified polyurethane hot melt adhesive provided by the present invention is a liquid or paste at room temperature, and has the characteristics of low melt viscosity, room temperature dispensing, high initial bonding strength and final bonding strength, fast curing speed and electrical disassembly.
[0023] In a preferred embodiment, the raw materials for preparing the acrylate-modified polyurethane hot melt adhesive contain polyisocyanate compounds, low-viscosity polyol compounds, acrylate compounds, ionic liquids, photoinitiators, and optional rheology modifiers, silane coupling agents, water absorbents, and catalysts, and the molar equivalent ratio of isocyanate groups in the polyisocyanate compounds to hydroxyl groups in the low-viscosity polyol compounds is (2.5-5): 1. Among them, the molar equivalent ratio of isocyanate groups in the polyisocyanate compounds to hydroxyl groups in the low-viscosity polyol compounds can be specifically 2.5: 1, 3: 1, 3.5: 1, 4: 1, 4.5: 1, 5: 1 or any value therebetween.
[0024] In the present invention, the mass ratio of the total content of the polyisocyanate compound and the low-viscosity polyol compound to the content of the ionic liquid is preferably (3-40):1, specifically 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 7:1, 9:1, 11:1, 13:1, 15:1, 17:1, 19:1, 20:1, 22:1, 25:1, 28:1, 30:1, 32:1, 35:1, 38:1, 40:1 or any value therebetween. The mass ratio of the acrylate compound to the ionic liquid is preferably (0.3-18):1, specifically 0.3:1, 0.5:1, 1:1, 2:1, 5:1, 8:1, 10:1, 12:1, 15:1, 18:1 or any value therebetween. The mass ratio of the photoinitiator to the ionic liquid is preferably (0.005-2.5):1, specifically 0.005:1, 0.01:1, 0.05:1, 0.1:1, 0.5:1, 0.8:1, 1:1, 1.5:1, 2:1, 2.5:1 or any value therebetween. The mass ratio of the catalyst to the ionic liquid is preferably (0.005-1):1, specifically 0.005:1, 0.01:1, 0.05:1, 0.1:1, 0.3:1, 0.5:1, 0.8:1, 1:1 or any value therebetween. The mass ratio of the rheology modifier to the ionic liquid is preferably (0-5):1, specifically 0, 0.1:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1 or any value therebetween. The mass ratio of the silane coupling agent to the ionic liquid is preferably (0-1.5):1, specifically 0, 0.005:1, 0.01:1, 0.05:1, 0.1:1, 0.3:1, 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1 or any value therebetween. The mass ratio of the water absorbent to the ionic liquid is preferably (0-1):1, specifically 0, 0.005:1, 0.01:1, 0.05:1, 0.1:1, 0.3:1, 0.5:1, 0.8:1, 1:1 or any value therebetween.
[0025] In a preferred embodiment, based on the total weight of the raw materials for preparing the acrylate-modified polyurethane hot melt adhesive, the total content of the polyisocyanate compound and the low-viscosity polyol compound is 45-80%, such as 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value therebetween; the content of the acrylate compound is 5-35%, such as 3%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35% or any value therebetween; the content of the ionic liquid is 2-15%, such as 2%, 5%, 8%, 10%, 12%, 15% or any value therebetween; the content of the photoinitiator is 10% to 25%, such as 10% to 3 ... The content of the rheology modifier is 2-10%, such as 2%, 5%, 8%, 10% or any value therebetween; the content of the silane coupling agent is 0.1-3%, such as 0.1%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3% or any value therebetween; the content of the water absorbent is 0.1-2%, such as 0.1%, 0.5%, 0.8%, 1%, 1.5%, 2% or any value therebetween; the content of the catalyst is 0.1-2%, such as 0.1%, 0.5%, 0.8%, 1%, 1.5%, 2% or any value therebetween.
[0026] In the present invention, the polyisocyanate compound is a compound with two or more isocyanate groups at the terminal of the molecular chain, and can be specifically an aromatic isocyanate and / or an aliphatic isocyanate, and specific examples thereof include but are not limited to at least one of isophorone diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, diphenylmethane-4,4'-diisocyanate, diphenylmethane-2,4'-diisocyanate, hydrogenated xylene diisocyanate, 1,5-naphthalene diisocyanate, 1,5-pentane diisocyanate, 1,4-phenylene diisocyanate, xylene diisocyanate, tetramethylxylene diisocyanate, norbornane diisocyanate, lysine diisocyanate, triphenylmethane triisocyanate, thiophosphoric acid triphenyl isocyanate and 1,6,11-undecane triisocyanate.
[0027] In the present invention, the number average molecular weight of the low viscosity polyol compound is preferably 400-6000 g / mol, such as 400, 500, 800, 1000, 1200, 1500, 1800, 2000, 2500, 3000, 3500, 4000, 4500, 5000, 5500, 6000 g / mol or any value therebetween. The low viscosity polyol compound can be any existing polyol compound having a glass transition temperature of 0°C or less and a melting point of 40°C or less, and specific examples thereof include but are not limited to at least one of liquid polyester polyol, liquid polyether polyol, liquid polycarbonate polyol, liquid polycaprolactone polyol, fatty acid dimer diol, castor oil derivative polyol and hydroxy-terminated polybutadiene polyol.
[0028] In the present invention, the acrylate compound can be various existing photocurable acrylate monomers, such as octadecyl acrylate, tetramethylene glycol acrylate, dodecyl acrylate, 2-phenoxyethyl acrylate, isodecyl acrylate, isooctyl acrylate, tridecyl acrylate, trimethylolpropane formal acrylate, monoacrylate of methoxy polyethylene glycol, alkoxylated tetramethylene glycol acrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, diethylene glycol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, tetraethylene glycol diacrylate, triethylene glycol diacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate and 1,3-butanediol dimethacrylate.
[0029] In the present invention, the melting point of the ionic liquid is preferably below 25°C, such as 25°C, 23°C, 20°C, 18°C, 15°C, 13°C, 10°C, 8°C, 5°C, 2°C, 0°C, -5°C, -10°C, -15°C, -20°C, -30°C, -40°C, etc. The ionic liquid is composed of cations and anions. The cations are preferably selected from at least one of imidazole cations, pyrrole cations, quaternary ammonium salt cations, quaternary phosphonium salt cations, pyrrolidine cations and piperidine cations. The anions are preferably selected from at least one of trifluoromethanesulfonate anions, tetrafluoroborate anions, hexafluorophosphate anions, bisfluoromethanesulfonyl imide anions, hydrogen sulfate anions, ethyl sulfate anions and p-toluenesulfonate anions. Specific examples of the above-mentioned ionic liquids include, but are not limited to: 1-butyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-2,3-dimethylimidazolium trifluoromethanesulfonate, 1-octyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-propyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-2,3-dimethylimidazolium tetrafluoroborate, 1-propyl-2,3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium ethyl sulfate, 1-ethyl-2,3-dimethylimidazolium ethyl sulfate, 1-butyl-3-methylimidazolium bis(trifluoromethane) at least one of bis(trifluoromethanesulfonyl)imide salts, 1,3-diethylimidazolium bis(trifluoromethanesulfonyl)imide salts, 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salts, 1-hexyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salts, 1,2-dimethyl-3-propylimidazolium bis(trifluoromethanesulfonyl)imide salts, 1-ethyl-2,3-dimethylimidazolium bis(trifluoromethanesulfonyl)imide salts, N-butylpyridinium tetrafluoroborate, hexyltriethylammonium bis(trifluoromethanesulfonyl)imide salts, methyltrioctylphosphonium bis(trifluoromethanesulfonyl)imide salts, N-butyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salts, N-butyl-N-methylpyrrolidine trifluoromethanesulfonate salts and N-propyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide salts.
[0030] In the present invention, the photoinitiator can be any of the existing various compounds that absorb energy in the ultraviolet light region or the visible light region to generate free radicals to initiate the polymerization reaction of acrylic functional groups, such as at least one of benzophenone compounds, acetophenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, benzoin ether compounds and thioxanthone.
[0031] In the present invention, the rheology modifier is preferably fumed silica, and specific examples thereof include but are not limited to at least one of AEROSIL A150, AEROSIL A200, AEROSIL A300, AEROSIL A380, AEROSIL R972, AEROSIL R974, AEROSIL R202, AEROSIL R812, HDK V15, HDK N20, HDK T30, HDK T40, HDK H13L, HDK H15, HDK H15L, HDK H16, HDK H17, HDK H18, HDK H2000, HDK H20, HDK H21, HDK H30, HDK H30RM, LM-150, M-5, E-5, EH-5, TS610, TS620, TS622, TS720, TS530 and TSUBOND. The specific surface area of the fumed silica is preferably 90 to 380 m 2 / g, specifically 90, 100, 120, 150, 180, 200, 220, 240, 260, 280, 300, 320, 340, 360, 380 m 2 / g or any value in between.
[0032] In the present invention, specific examples of the silane coupling agent include, but are not limited to: 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, At least one of 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropylmethyldimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane and 3-isocyanatepropyltrimethoxysilane.
[0033] In the present invention, the water absorbent may be selected from at least one of a molecular sieve desiccant, an oxazolidine dehydrating agent, p-toluenesulfonyl isocyanate and triethyl orthoformate.
[0034] In the present invention, the catalyst can be selected from at least one of dibutyltin dilaurate, stannous octoate, zinc isooctanoate, bismuth isooctanoate, triethylamine, diethylenetriamine, triethylenediamine, N-ethylmorpholine and 2,2-dimorpholinyl diethyl ether.
[0035] The preparation method of the acrylate modified polyurethane hot melt adhesive provided by the present invention comprises the following steps: S1, dehydrating a low-viscosity polyol compound and an ionic liquid as well as an optional rheology modifier, a silane coupling agent and a water absorbent to obtain a pretreated product; S2, stirring the pretreated product, a polyisocyanate compound and an optional catalyst at 70 to 90° C. for 1 to 5 hours to obtain a prepolymer containing a polyurethane prepolymer mixture; S3, uniformly mixing the prepolymer with an acrylate compound and a photoinitiator to obtain the acrylate modified polyurethane hot melt adhesive.
[0036] In the present invention, in step S1, the conditions for the dehydration treatment preferably include a temperature of 100-120°C, such as 100°C, 102°C, 104°C, 106°C, 108°C, 110°C, 112°C, 114°C, 116°C, 118°C, 120°C or any value therebetween; a rotation speed of 100-200r / min, such as 100r / min, 110r / min, 120r / min, 130r / min, 140r / min, 150r / min, 160r / min, 170r / min, 180r / min, 190r / min, 200r / min or any value therebetween; and a time of 1-5h, such as 1h, 2h, 3h, 4h, 5h or any value therebetween.
[0037] In the present invention, in step S2, the temperature of the stirring reaction is preferably 70-90°C, specifically 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C, 90°C or any value therebetween; the speed of the stirring reaction is preferably 100-200r / min, specifically 100r / min, 110r / min, 120r / min, 130r / min, 140r / min, 150r / min, 160r / min, 170r / min, 180r / min, 190r / min, 200r / min or any value therebetween; the time of the stirring reaction is preferably 1-5h, specifically 1h, 2h, 3h, 4h, 5h or any value therebetween.
[0038] In the present invention, in step S3, the mixing conditions preferably include a temperature of 70 to 90°C, specifically 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C, 90°C or any value therebetween; a stirring speed of 100 to 200 r / min, specifically 100 r / min, 110 r / min, 120 r / min, 130 r / min, 140 r / min, 150 r / min, 160 r / min, 170 r / min, 180 r / min, 190 r / min, 200 r / min or any value therebetween; and a time of 30 min to 2 h, specifically 30 min, 40 min, 50 min, 60 min, 80 min, 100 min, 120 min or any value therebetween.
[0039] The invention also provides application of the acrylate modified polyurethane hot melt adhesive in bonding electronic products.
[0040] The bonding substrate used in the acrylate modified polyurethane hot melt adhesive provided by the present invention is a conductive substrate.
[0041] The present invention will be described in detail below by way of examples. The examples of the embodiments are intended to explain the present invention and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0042] Example 1
[0043] By weight, 15.96 g (5.320 mmol) of a liquid polyether diol with a number average molecular weight of 3000 (Dow Voranol WD2130; Tg <0°C; melting point <25°C), 31.92 g (15.960 mmol) of a liquid polyester diol with a number average molecular weight of 2000 (stepanpol PH-56; Tg = -15°C; melting point <25°C), 6.00 g of 1-ethyl-3-methylimidazolium tetrafluoroborate (melting point = 15°C), 4.5 g of fumed silica HDK H18, 0.3 g of 3-Aminopropyltrimethoxysilane and 0.4g water absorbent AdditiveOF were heated to 110°C, vacuum dehydrated for 2h under stirring conditions at 150r / min, then cooled to 80°C, 18.62g (74.48mmol) of diphenylmethane-4,4'-diisocyanate (MDI) and 0.3g of dibutyltin dilaurate were added, and the mixture was reacted for 2h under stirring conditions at 150r / min, and then 2.0g of photoinitiator ITX, 10.0g of 1,6-hexanediol diacrylate and 10.0g of trimethylolpropane formal acrylate were added, mixed for 1h under stirring conditions at 150r / min, and then discharged to obtain acrylate-modified polyurethane hot melt adhesive, which was vacuum sealed and stored away from light.
[0044] Example 2
[0045] By weight, 24.89 g (7.111 mmol) of a liquid polyester diol with a number average molecular weight of 3500 (Dynacoll 7230; Tg = -30 ° C; melting point < 25 ° C), 14.22 g (7.111 mmol) of a liquid polyether diol with a number average molecular weight of 2000 (Dow Voranol 2120; Tg < 0 ° C; melting point < 25 ° C), 10.00 g of 1-butyl-3-methylimidazolium tetrafluoroborate (melting point = -71 ° C), 6.5 g of fumed silica TS-610, 0.7 g of 3-mercaptopropyltrimethoxysilane and 1.2 g of a water absorbent additive were added. TI, heated to 110 ° C, vacuum dehydrated at 150 r / min stirring condition for 2 h, then cooled to 80 ° C, added 8.89 g (35.56 mmol) of diphenylmethane-4,4'-diisocyanate (MDI) and 0.6 g of stannous octoate, reacted at 150 r / min stirring condition for 2 h, then added 3.0 g of photoinitiator 369, 15.0 g of triethylene glycol diacrylate and 15.0 g of tetrahydrofuran acrylate, mixed at 150 r / min stirring condition for 1 h and then discharged to obtain acrylate modified polyurethane hot melt adhesive, which was vacuum sealed and stored away from light.
[0046] Example 3
[0047] By weight, 42.10 g (14.032 mmol) of a liquid polycarbonate diol with a number average molecular weight of 3000 (Kuraraypolyol C3090; Tg = -42 ° C; melting point <25 ° C), 14.03 g (14.032 mmol) of a liquid polyether diol with a number average molecular weight of 1000 (Dow Voranol 220-110; Tg <0 ° C; melting point <25 ° C), 4.00 g of hexyltriethylammonium bis (trifluoromethanesulfonyl) imide salt (melting point = 20 ° C), 2.5 g of fumed silica AEROSIL R202, 0.5 g of 3-glycidoxypropyltrimethoxysilane and 1.0 g of a water absorbent Additive TI, heated to 110 ° C, vacuum dehydrated for 2 h under stirring conditions at 150 r / min, then cooled to 80 ° C, added 23.57 g (140.317 mmol) of hexamethylene diisocyanate (HDI) and 1.2 g of zinc isooctanoate, reacted for 2 h under stirring conditions at 150 r / min, then added 1.1 g of photoinitiator 819, 5.0 g of triethylene glycol diacrylate, and 5.0 g of dodecyl acrylate, mixed for 1 h under stirring conditions at 150 r / min, and then discharged to obtain acrylate-modified polyurethane hot melt adhesive, which was vacuum sealed and stored away from light.
[0048] Example 4
[0049] By weight, 29.82 g (14.908 mmol) of a liquid polyester diol with a number average molecular weight of 2000 (Stepanpol PH-56; Tg = -15 ° C; melting point <25 ° C), 14.91 g (14.908 mmol) of a liquid polycarbonate diol with a number average molecular weight of 1000 (Kuraray polyol C1050; Tg <0 ° C; melting point <25 ° C), 13.00 g of N-butyl-N-methylpyrrolidine bisfluorosulfonyl imide salt (melting point = -15 ° C), 3.5 g of fumed silica AEROSIL R972, 1.5 g of 3-isocyanate propyltrimethoxysilane and 0.8 g of water absorbent Additive TI, heated to 110 ° C, vacuum dehydrated for 2 h under stirring conditions at 150 r / min, then cooled to 80 ° C, added 26.48 g (119.263 mmol) of isophorone diisocyanate (IPDI) and 1.5 g of bismuth isooctanoate, reacted for 2 h under stirring conditions at 150 r / min, then added 0.5 g of photoinitiator TPO, 4.0 g of neopentyl glycol diacrylate and 4.0 g of isooctyl acrylate, mixed for 1 h under stirring conditions at 150 r / min, and then discharged to obtain acrylate-modified polyurethane hot melt adhesive, which was vacuum sealed and stored away from light.
[0050] Example 5
[0051] By weight, 28.95 g (8.272 mmol) of a liquid polyester diol with a number average molecular weight of 3500 (Dynacoll 7210; Tg = -15 ° C; melting point <25 ° C), 16.54 g (16.544 mmol) of a liquid polycarbonate diol with a number average molecular weight of 1000 (PLACCEL 210N; Tg = -17 ° C; melting point = 32-37 ° C), 8.00 g of 1,3-diethylimidazole bis (trifluoromethanesulfonyl) imide salt (melting point = 12.4 ° C), 4.0 g of fumed silica HDK H20, 1.7 g of 3-acryloxypropyltrimethoxysilane and 0.5 g of water absorbent Additive TI, heated to 110 ° C, vacuum dehydrated at 150 r / min stirring condition for 2 h, then cooled to 80 ° C, added 19.50 g (74.446 mmol) dicyclohexylmethane-4,4'-diisocyanate (HMDI) and 1.3 g stannous octoate, reacted at 150 r / min stirring condition for 2 h, then added 1.5 g photoinitiator 184, 10.0 g diethylene glycol diacrylate and 8.0 g tridecyl acrylate, mixed at 150 r / min stirring condition for 1 h and then discharged to obtain acrylate modified polyurethane hot melt adhesive, which was vacuum sealed and stored away from light.
[0052] Comparative Example 1
[0053] By weight, 39.41 g (13.137 mmol) of a liquid polycarbonate diol with a number average molecular weight of 3000 (Kuraraypolyol C3090; Tg = -42 ° C; melting point <25 ° C), 8.76 g (4.379 mmol) of a liquid polyether diol with a number average molecular weight of 2000 (Dow Voranol 2120; Tg <0 ° C; melting point <25 ° C), 4.38 g (4.379 mmol) of a liquid polyether diol with a number average molecular weight of 1000 (Dow Voranol 220-110; Tg <0 ° C; melting point <25 ° C), 5.5 g of fumed silica HDK H17, 0.3 g of 3-aminopropyltrimethoxysilane and 0.5 g of a water absorbent Additive OF, heated to 110 ° C, vacuum dehydrated for 2 h under stirring conditions at 150 r / min, then cooled to 80 ° C, 41.05 g (164.211 mmol) of diphenylmethane-4,4'-diisocyanate (MDI) and 0.1 g of dibutyltin dilaurate were added, and the reaction was carried out under stirring conditions at 150 r / min for 2 h before discharging to obtain a reference polyurethane hot melt adhesive, which was vacuum sealed and stored.
[0054] Comparative Example 2
[0055] By weight, 42.11 g (12.031 mmol) of polyester diol with a number average molecular weight of 3500 (Evonik Dynacoll 7380; melting point = 70°C), 24.06 g (12.031 mmol) of liquid polyether diol with a number average molecular weight of 2000 (Dow Voranol 2120; Tg <0°C; melting point <25°C), 10.0 g of thermoplastic acrylic resin BM751 (Tg = 49°C), 5.0 g of 1-ethyl-3-methylimidazolium trifluoromethanesulfonate (melting point = -12°C), 5.0 g of propylene carbonate, 1.0 g of 3-mercaptopropyltrimethoxysilane and 0.5 g of water absorbent Additive OF, heated to 110 ° C, vacuum dehydrated for 2 h under stirring conditions at 150 r / min, then cooled to 80 ° C, 12.03 g (48.123 mmol) of diphenylmethane-4,4'-diisocyanate (MDI) and 0.3 g of stannous octoate were added, and the reaction was carried out under stirring conditions at 150 r / min for 2 h before discharging the material to obtain a reference polyurethane hot melt adhesive, which was vacuum sealed and stored.
[0056] Comparative Example 3
[0057] The polyurethane hot melt adhesive was prepared according to the method of Example 1, except that the liquid polyether diol and the liquid polyester diol were replaced by the same molar amount of solid polyester diol and solid polycarbonate diol with a melting point higher than 40° C., respectively. The other conditions were the same as those of Example 1, as follows:
[0058] By weight, 15.96 g (5.320 mmol) of a solid polyester diol with a number average molecular weight of 3000 (Hoopol F-580; melting point = 50°C), 31.92 g (15.960 mmol) of a solid polycarbonate diol with a number average molecular weight of 2000 (UH-CARB200; melting point = 50°C), 6.00 g of 1-ethyl-3-methylimidazolium tetrafluoroborate (melting point = 15°C), 4.5 g of fumed silica HDK H18, 0.3 g of 3-aminopropyltrimethoxysilane and 0.4 g of a water absorbent additive were added. OF, heated to 110 ° C, vacuum dehydrated for 2 h under stirring conditions at 150 r / min, then cooled to 80 ° C, added 18.62 g (74.48 mmol) of diphenylmethane-4,4'-diisocyanate (MDI) and 0.3 g of dibutyltin dilaurate, reacted for 2 h under stirring conditions at 150 r / min, then added 2.0 g of photoinitiator ITX, 10.0 g of 1,6-hexanediol diacrylate, and 10.0 g of trimethylolpropane formal acrylate, mixed for 1 h under stirring conditions at 150 r / min, and then discharged to obtain a reference polyurethane hot melt adhesive, which was vacuum sealed and stored away from light.
[0059] Comparative Example 4
[0060] The polyurethane hot melt adhesive was prepared according to the method of Example 1, except that the polyisocyanate compound was adjusted so that the molar equivalent ratio of the isocyanate group in the polyisocyanate compound of Example 1 to the hydroxyl group in the low-viscosity polyol compound was reduced from 3.5:1 to 1.8:1. At this time, the polyurethane prepolymer could not achieve isocyanate double end-capping, as follows:
[0061] By weight, 18.47 g (6.157 mmol) of a liquid polyether diol with a number average molecular weight of 3000 (Dow Voranol WD2130; Tg <0°C; melting point <25°C), 36.94 g (18.472 mmol) of a liquid polyester diol with a number average molecular weight of 2000 (stepanpol PH-56; Tg = -15°C; melting point <25°C), 6.00 g of 1-ethyl-3-methylimidazolium tetrafluoroborate (melting point = 15°C), 4.5 g of fumed silica HDK H18, 0.3 g of 3-Aminopropyltrimethoxysilane and 0.4g water absorbent AdditiveOF were heated to 110°C, vacuum dehydrated for 2h under stirring conditions at 150r / min, then cooled to 80°C, 11.08g (44.333mmol) of diphenylmethane-4,4'-diisocyanate (MDI) and 0.3g of dibutyltin dilaurate were added, and the mixture was reacted for 2h under stirring conditions at 150r / min, and then 2.0g of photoinitiator ITX, 10.0g of 1,6-hexanediol diacrylate and 10.0g of trimethylolpropane formal acrylate were added, mixed for 1h under stirring conditions at 150r / min, and then discharged to obtain a reference polyurethane hot melt adhesive, which was vacuum sealed and stored away from light.
[0062] Comparative Example 5
[0063] The polyurethane hot melt adhesive was prepared according to the method of Example 1, except that no ionic liquid was added, and the other conditions were the same as those of Example 1, as follows:
[0064] By weight, 15.96 g (5.320 mmol) of a liquid polyether diol with a number average molecular weight of 3000 (Dow Voranol WD2130; Tg <0°C; melting point <25°C), 31.92 g (15.960 mmol) of a liquid polyester diol with a number average molecular weight of 2000 (Stepanpol PH-56; Tg = -15°C; melting point <25°C), 4.5 g of fumed silica HDK H18, 0.3 g of 3-aminopropyltrimethoxysilane and 0.4 g of a water absorbent additive were added. OF, heated to 110 ° C, vacuum dehydrated for 2 h under stirring conditions at 150 r / min, then cooled to 80 ° C, 18.62 g (74.48 mmol) of diphenylmethane-4,4'-diisocyanate (MDI) and 0.3 g of dibutyltin dilaurate were added, and the mixture was reacted for 2 h under stirring conditions at 150 r / min. Then, 2.0 g of photoinitiator ITX, 10.0 g of 1,6-hexanediol diacrylate and 10.0 g of trimethylolpropane formal acrylate were added, and the mixture was mixed for 1 h under stirring conditions at 150 r / min, and then discharged to obtain a reference polyurethane hot melt adhesive, which was vacuum sealed and stored away from light.
[0065] Comparative Example 6
[0066] A polyurethane hot melt adhesive was prepared according to the method of Example 1, except that 1,6-hexanediol diacrylate and trimethylolpropane formal acrylate were not added, and the other conditions were the same as those of Example 1, as follows:
[0067] By weight, 15.96 g (5.320 mmol) of a liquid polyether diol with a number average molecular weight of 3000 (Dow Voranol WD2130; Tg <0°C; melting point <25°C), 31.92 g (15.960 mmol) of a liquid polyester diol with a number average molecular weight of 2000 (stepanpol PH-56; Tg = -15°C; melting point <25°C), 6.00 g of 1-ethyl-3-methylimidazolium tetrafluoroborate (melting point = 15°C), 4.5 g of fumed silica HDK H18, 0.3 g of 3-Aminopropyltrimethoxysilane and 0.4g water absorbent AdditiveOF were heated to 110°C, vacuum dehydrated for 2h at 150r / min stirring, then cooled to 80°C, 18.62g (74.48mmol) of diphenylmethane-4,4'-diisocyanate (MDI) and 0.3g of dibutyltin dilaurate were added, reacted for 2h at 150r / min stirring, then 2.0g of photoinitiator ITX was added, mixed for 1h at 150r / min stirring, and then discharged to obtain a reference polyurethane hot melt adhesive, which was vacuum sealed and stored away from light.
[0068] Comparative Example 7
[0069] The polyurethane hot melt adhesive was prepared according to the method of Example 1, except that the addition amount of 1,6-hexanediol diacrylate and trimethylolpropane formal acrylate was increased to 40.0 g. The rest was the same as in Example 1, specifically as follows:
[0070] By weight, 15.96 g (5.320 mmol) of a liquid polyether diol with a number average molecular weight of 3000 (Dow Voranol WD2130; Tg <0°C; melting point <25°C), 31.92 g (15.960 mmol) of a liquid polyester diol with a number average molecular weight of 2000 (stepanpol PH-56; Tg = -15°C; melting point <25°C), 6.00 g of 1-ethyl-3-methylimidazolium tetrafluoroborate (melting point = 15°C), 4.5 g of fumed silica HDK H18, 0.3 g of 3-Aminopropyltrimethoxysilane and 0.4g water absorbent AdditiveOF were heated to 110°C, vacuum dehydrated for 2h under stirring conditions at 150r / min, then cooled to 80°C, 18.62g (74.48mmol) of diphenylmethane-4,4'-diisocyanate (MDI) and 0.3g of dibutyltin dilaurate were added, and the mixture was reacted for 2h under stirring conditions at 150r / min, and then 2.0g of photoinitiator ITX, 40.0g of 1,6-hexanediol diacrylate and 40.0g of trimethylolpropane formal acrylate were added, mixed for 1h under stirring conditions at 150r / min, and then discharged to obtain a reference polyurethane hot melt adhesive, which was vacuum sealed and stored away from light.
[0071] Test Case
[0072] The samples of the embodiment and the comparative example were subjected to comparative tests in the following manner:
[0073] (1) Viscosity at 25°C: The polyurethane hot melt adhesive samples obtained in the above embodiments and comparative examples were respectively sampled into a cone-plate viscometer, and the viscosity of the adhesive was tested at 25°C and 1 rpm using the cone-plate viscometer. The results are shown in Table 1.
[0074] (2) Bonding strength at different curing times: The polyurethane hot melt adhesive obtained in the above embodiments and comparative examples was dispensed at room temperature using a dispensing machine (if it was solid at room temperature, the dispensing temperature was set at 110°C), a rectangular adhesive line of 25 mm × 4 mm was applied on a stainless steel substrate, and then a 365 nm UV-LED light source was used to irradiate the adhesive at 2000 mJ / cm 2After the irradiation, another stainless steel substrate was bonded to the stainless steel substrate. After the bonding, the sample was cured in an environment of 25°C and 50% RH for 5 minutes, 30 minutes and 48 hours. Then, a universal material testing machine was used to run the prepared bonding sample along the shear direction at a speed of 10 mm / min until the bonding of the sample failed. The maximum force value displayed by the recording instrument was calculated, and the shear bonding strength of the polyurethane hot melt adhesive to the stainless steel substrate before power was applied was calculated in combination with the bonding area. The results are shown in Table 1.
[0075] (3) Adhesion strength after power on: The polyurethane hot melt adhesive obtained in the above embodiments and comparative examples was dispensed at room temperature using a dispensing machine (if it is solid at room temperature, the dispensing temperature was set at 110°C), and a rectangular adhesive line of 25 mm × 4 mm was applied on a stainless steel substrate. Then, a 365 nm UV-LED light source was used to irradiate the adhesive at 2000 mJ / cm 2 Energy, after irradiation, another stainless steel substrate is bonded on the stainless steel substrate. After bonding, the sample is cured in an environment of 25°C and 50% RH for 48 hours. Then, the positive and negative wires of the DC power supply are clamped at both ends of the shear sample, and the power is turned on for a certain time at a certain voltage. After the power is turned on, the shear sample is removed, and the universal material testing machine is used to run the prepared bonding sample along the shear direction at a speed of 10mm / min until the sample fails to bond. The maximum force value displayed by the recording instrument is recorded, and the shear bonding strength of the polyurethane hot melt adhesive to the stainless steel substrate after power on is calculated in combination with the bonding area. The results are shown in Table 1.
[0076] Table 1
[0077]
[0078] As can be seen from the results of Table 1, the acrylate-modified polyurethane hot melt adhesive provided by the present invention has a lower viscosity at room temperature, and can be directly dispensed at room temperature, which significantly improves the defect that the reactive polyurethane hot melt adhesive needs to be heated for gluing, increases the convenience of using the adhesive, and reduces the risk of being scalded by the operator during the use of the heating equipment. According to practical experience, if the bonding strength at room temperature is less than 2.0MPa, it means that the adhesive is removable, otherwise it is not removable. As can be seen from the results of Table 1, the acrylate-modified polyurethane hot melt adhesive provided by the present invention can quickly establish a higher initial bonding strength after UV light, has the function of realizing preliminary positioning in a short time, has excellent final bonding strength after being fully cured, and the bonding strength of the adhesive can be significantly attenuated after power-on, and can even fall off directly, with excellent power-on disassembly performance. In summary, the acrylate-modified polyurethane hot melt adhesive provided by the present invention has a low melt viscosity, can be dispensed at room temperature, has high initial bonding strength and final bonding strength, fast curing speed, and has a disassembly function under power-on conditions, and has broad practical application prospects.
[0079] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. An acrylate modified polyurethane hot melt adhesive, characterized in that: The viscosity of the acrylate-modified polyurethane hot melt adhesive at 25°C is in the range of 1000 to 150000 cps, and the attenuation rate of the bonding strength is above 80% after a voltage of 1 to 100 V is applied. The acrylate-modified polyurethane hot melt adhesive contains a polyurethane prepolymer mixture, an acrylate compound, an ionic liquid and a photoinitiator. Both ends of the prepolymer contained in the polyurethane prepolymer mixture are capped with isocyanate. The polyol structural unit contained in the polyurethane prepolymer mixture is derived from a low-viscosity polyol compound having a glass transition temperature of less than 0°C and a melting point of less than 40°C. The mass ratio of the polyurethane prepolymer mixture to the acrylate compound is (1.5 to 9):
1.
2. The acrylate-modified polyurethane hot melt adhesive according to claim 1, characterized in that: The raw materials for preparing the acrylate-modified polyurethane hot melt adhesive contain polyisocyanate compounds, low-viscosity polyol compounds, acrylate compounds, ionic liquids, photoinitiators, and optional rheology modifiers, silane coupling agents, water absorbents, and catalysts. The molar equivalent ratio of isocyanate groups in the polyisocyanate compounds to hydroxyl groups in the low-viscosity polyol compounds is (2.5-5):
1.
3. The acrylate-modified polyurethane hot melt adhesive according to claim 2, characterized in that: Based on the total weight of the raw materials for preparing the acrylate-modified polyurethane hot melt adhesive, the total content of the polyisocyanate compound and the low-viscosity polyol compound is 45-80%, the content of the acrylate compound is 5-35%, the content of the ionic liquid is 2-15%, the content of the photoinitiator is 0.1-5%, the content of the rheology modifier is 2-10%, the content of the silane coupling agent is 0.1-3%, the content of the water absorbent is 0.1-2%, and the content of the catalyst is 0.1-2%.
4. The acrylate modified polyurethane hot melt adhesive according to claim 2, characterized in that: The polyisocyanate compound is selected from at least one of isophorone diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, diphenylmethane-4,4'-diisocyanate, diphenylmethane-2,4'-diisocyanate, hydrogenated xylylene diisocyanate, 1,5-naphthalene diisocyanate, 1,5-pentane diisocyanate, 1,4-phenylene diisocyanate, xylylene diisocyanate, tetramethylxylene diisocyanate, norbornane diisocyanate, lysine diisocyanate, triphenylmethane triisocyanate, thiophosphoric acid triphenyl isocyanate and 1,6,11-undecane triisocyanate.
5. The acrylate modified polyurethane hot melt adhesive according to claim 2, characterized in that: The number average molecular weight of the low-viscosity polyol compound is 400-6000 g / mol; the low-viscosity polyol compound is selected from at least one of liquid polyester polyol, liquid polyether polyol, liquid polycarbonate polyol, liquid polycaprolactone polyol, fatty acid dimer diol, castor oil derivative polyol and terminal hydroxyl polybutadiene polyol.
6. The acrylate-modified polyurethane hot melt adhesive according to claim 2, characterized in that: The acrylate compound is selected from at least one of octadecyl acrylate, tetramethylene glycol acrylate, dodecyl acrylate, 2-phenoxyethyl acrylate, isodecyl acrylate, isooctyl acrylate, tridecyl acrylate, trimethylolpropane formal acrylate, monoacrylate of methoxy polyethylene glycol, alkoxylated tetramethylene glycol acrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, diethylene glycol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, tetraethylene glycol diacrylate, triethylene glycol diacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate and 1,3-butanediol dimethacrylate.
7. The acrylate-modified polyurethane hot melt adhesive according to claim 2, characterized in that: The melting point of the ionic liquid is below 25°C; Preferably, the ionic liquid is composed of organic cations and anions, the organic cations are selected from at least one of imidazole cations, pyrrole cations, quaternary ammonium salt cations, quaternary phosphonium salt cations, pyrrolidine cations and piperidine cations, and the anions are selected from at least one of trifluoromethanesulfonate anions, tetrafluoroborate anions, hexafluorophosphate anions, bisfluoromethanesulfonyl imide anions, hydrogen sulfate anions, ethyl sulfate anions and p-toluenesulfonate anions; Preferably, the ionic liquid is selected from 1-butyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-2,3-dimethylimidazolium trifluoromethanesulfonate, 1-octyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-propyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-2,3-dimethylimidazolium tetrafluoroborate, 1-propyl-2,3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium ethyl sulfate, 1-ethyl-2,3-dimethylimidazolium ethyl sulfate, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide at least one of salt, 1,3-diethylimidazolium bis(trifluoromethanesulfonyl)imide salt, 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, 1-hexyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, 1,2-dimethyl-3-propylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-2,3-dimethylimidazolium bis(trifluoromethanesulfonyl)imide salt, N-butylpyridinium tetrafluoroborate, hexyltriethylammonium bis(trifluoromethanesulfonyl)imide salt, methyltrioctylphosphonium bis(trifluoromethanesulfonyl)imide salt, N-butyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, N-butyl-N-methylpyrrolidine trifluoromethanesulfonate and N-propyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide salt.
8. The acrylate-modified polyurethane hot melt adhesive according to claim 2, characterized in that: The photoinitiator is selected from at least one of benzophenone compounds, acetophenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, benzoin ether compounds and thioxanthone.
9. The acrylate-modified polyurethane hot melt adhesive according to claim 2, characterized in that: The catalyst is selected from at least one of dibutyltin dilaurate, stannous octoate, zinc isooctanoate, bismuth isooctanoate, triethylamine, diethylenetriamine, triethylenediamine, N-ethylmorpholine and 2,2-dimorpholinyl diethyl ether.
10. The acrylate-modified polyurethane hot melt adhesive according to claim 2, characterized in that: The rheology modifier is fumed silica.
11. The acrylate-modified polyurethane hot melt adhesive according to claim 2, characterized in that: The silane coupling agent is selected from 3-mercaptopropyl trimethoxysilane, 3-mercaptopropyl triethoxysilane, 3-mercaptopropyl methyl dimethoxysilane, 3-mercaptopropyl methyl diethoxysilane, 3-glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl triethoxysilane, 3-glycidoxypropyl methyl dimethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3-(2 -aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropylmethyldimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane and at least one of 3-isocyanatepropyltrimethoxysilane.
12. The acrylate-modified polyurethane hot melt adhesive according to claim 2, characterized in that: The water absorbent is selected from at least one of a molecular sieve desiccant, an oxazolidine dehydrating agent, p-toluenesulfonyl isocyanate and triethyl orthoformate.
13. The method for preparing the acrylate modified polyurethane hot melt adhesive according to any one of claims 1 to 12, characterized in that: The method comprises the following steps: S1, dehydrating the low-viscosity polyol compound and the ionic liquid and the optional rheology modifier, silane coupling agent and water absorbent to obtain a pretreated product; S2, stirring the pretreated product, the polyisocyanate compound and the optional catalyst at 70-90° C. for 1-5 hours to obtain a prepolymer containing a polyurethane prepolymer mixture; S3. Evenly mix the prepolymer, the acrylate compound and the photoinitiator to obtain the acrylate-modified polyurethane hot melt adhesive.
14. Use of the acrylate modified polyurethane hot melt adhesive according to any one of claims 1 to 12 in bonding electronic products.
Citation Information
Patent Citations
Debondable reactive hot melt adhesives
CN107207938A
High-strength moisture and light double-cured polyurethane adhesive as well as preparation method and application method thereof
CN108102558A
Cited By
Adhesive mass, adhesive tape, bonded composite, and method for electrically releasing the bonded composite
EP4790076A1